Transverse field muon-spin rotation measurement of the topological anomaly in a thin film of MnSi - Lancaster, T; Xiao, F; Salman, Z; Thomas, I; Blundell, S; Pratt, F; Clark, S; Prokscha, T; Suter, A; Zhang, S; Baker, A; Hesjedal, T (2015)
We present the results of transverse-field muon-spin rotation measurements on an epitaxially grown 40 nm-thick film of MnSi on Si(111) in the region of the field-temperature phase diagram where a skyrmion phase has been observed in the bulk. We identify changes in the quasistatic magnetic field distribution sampled by the muon, along with evidence for magnetic transitions around T ≈ 40 K and 30 K. Our results suggest that the cone phase is not the only magnetic texture realized in film samples for out-of-plane fields.